Awareness Regarding Newborn Danger Signs among Mothers in a Hospital of Rupandehi - Bhattarai, Sigma; Bhusal, Chetkant; Gurung, Saraj; Poudel, Nandini (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION: Newborn care is important for the proper development and healthy life of the baby and also in prevention of neonatal deaths from danger signs. The aim of the study was to find out the awareness regarding newborn danger signs among mothers in a hospital of Rupandehi. MATERIAL AND METHODS: Institutional based descriptive cross-sectional study was conducted to find out the awareness regarding newborn danger signs among 56 mothers selected through non probability purposive sampling method. Data was collected by using semi-structured interview schedule and was analyzed by using descriptive (frequency, percentage, mean, standard deviation) and inferential statistics (chi square) with Statistical Package for Social Science software (SPSS) version 20.0. The total duration of the study was from September 5, 2018 to September 19, 2018. RESULTS: The findings of the study revealed that half (50%) of the mothers had low level awareness regarding newborn danger signs. There was statistically significant association between mothers’ level of awareness regarding newborn danger signs with education status (p=0.001). CONCLUSION: Based on the study findings, it is concluded that still half of the respondents had low awareness regarding newborn danger signs. If all the mothers were aware regarding danger signs of their newborns. They can seek early management of the problems which help to reduce newborn morbidity and mortality. Thus, it is recommended to concerned authority to conduct awareness program to mothers regarding newborn danger signs.